A bailarina e seu tutu: criação e performance - Fernandes, Marina Carleial (2022)
The ballerina and her tutu: creation and performance presents reflections on the figure of the dancer and her tutu, a piece of clothing created in the romantic period of scenic dance and used for the first time in 1832 at “La Sylphide”. PaR, performance as research, was the meth odology chosen for this work because it is based on artistic experiences carried out during her manufacture between 2019 and 2021. In the first act of this work, I present a journey in time around the names and formations of dancers, then I describe my small collection of tutus and contextualize them in relation to the history of their creation. In the second act, I present the “Projeto Bailarinas”, a group of four dancers who carried out the performative actions ana lyzed in this dissertation. I dissert about women bodies in a context of dance by critically pro posing the use of tutus in a different way, namely inside out. Moreover, I analyze the im portance of the tutu in light of Baudrillard (1993) and Lepeki (2012) theories. For the third act, I present a compilation of artistic actions “Dancers will buy lunch in the center of Fortale za”, “Projeto Bailarinas participates in the IX Festival do Litoral Oeste in Itapipoca”, “Presen tation at Centro Cultural do Bom Jardim”, “Dancers in social connection” and “The tulle per formance”. With them, I discuss performance, memory, fashion and dance. Finally, to com plement my study, I bring contributions from several renowned dancers and authors like Schöpke (2009), Viana (2015), Mesquita, Pascolato, Guerreiro (2015), Greiner and Katz (2005), Bourcier (2001), Barthes (1967) among others. The materials produced during this research seek to answer the question “how to remain yourself a dancer today?”